PERANCANGAN APLIKASI E-COMMERCE ALAT TULIS PADA TOKO GRAHA BERBASIS WEBSITE - Nor Ramadha, Kartika; Mohammad Azri Harahap (Jurnal Teknik dan Science, 2024)
Graha is a store that sells office supplies, and to expand its marketing, a web-based e-commerce application was developed. The research method used in the design of this website is the System Development Life Cycle (SDLC). The programming languages used are HTML, CSS, JavaScript, PHP, and the database is MySQL. Based on tests conducted on various devices, it can be concluded that the Graha Store e-commerce website functions properly. The time required to access the website pages through a browser will vary depending on the internet connection used.